2015
DOI: 10.28932/jutisi.v1i3.400
|View full text |Cite
|
Sign up to set email alerts
|

Pengamanan Sertifikat Tanah Digital menggunakan Digital Signature SHA-512 dan RSA

Abstract: Land trading as investment is sometimes find some barriers or problems. One of the problems is illegal or misclaimed of the land certificate. Badan Pertanahan Nasional (BPN) and Pejabat Pembuat Akta Tanah (PPAT) as institutions and correlated parties in the process of land certificate making need a system to handle the problem of falsification land certificate. The purpose of this research is to make secure system of digital land certificate document with a data protection system to detect if there is a falsif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
0
2
0
6
Order By: Relevance
“…The other research is focused on Securing Digital Land Certificate by using SHA-512 and RSA Digital Signature. The result of this study indicates that the digital land certificate security system by using xref table can identify the presence or absence of significant changes in the digital certificate document file so it can be concluded that the system can verify the authenticity of the files by using SHA-512 and RSA by using the calculation process of xref table [5].…”
Section: Theoretical Framework 21 Review Of Literaturementioning
confidence: 82%
“…The other research is focused on Securing Digital Land Certificate by using SHA-512 and RSA Digital Signature. The result of this study indicates that the digital land certificate security system by using xref table can identify the presence or absence of significant changes in the digital certificate document file so it can be concluded that the system can verify the authenticity of the files by using SHA-512 and RSA by using the calculation process of xref table [5].…”
Section: Theoretical Framework 21 Review Of Literaturementioning
confidence: 82%
“…Metadata dari berkas jpeg/exif dienkripsi sebagai acuan verifikasi keaslian berkas. Penelitian tentang keamanan informasi yang bersifat deteksi ditemui dalam penelitian oleh Refialy [3]. Penelitian ini menunjukkan hash value dari dokumen pdf dapat digunakan sebagai identitas unik untuk mendeteksi integritas data pada dokumen yang diterima.…”
Section: Kata Kunci-file Fingerprint Hash Value Jpeg/exif Sha512 unclassified
“…Mengamankan data sertifikat tanah digital yakni dengan menggunakan digital signature SHA-512 sebagai proses hashing bagian xreftable dari file pdf sertifikat, selanjutnya dienkripsi dengan Algoritma RSA menjadi signature kemudian disisipi ke sebuah dokumen sertifikat tanah digital. Hal ini akan mengakibatkan sistem pengamanan sertifikat tanah digital dapat mengidentifikasi ada tidaknya perubahan yang terjadi pada file dokumen sertifikat digital sehinggadapat disimpulkan bahwa sistem dapat memverifikasi keaslian dari file dengan menggunakan SHA-512 dan RSA [9].…”
Section: Pendahuluanunclassified